Structural, Spectroscopic, and Magnetic Characterization of Cobalt(III) Oxide–Disodium Tetraborate Glasses. (1st November 2016) - Pop, L.; Culea, E.; Bosca, M.; Pascuta, P.
ABSTRACT: Co2 O3 –Na2 B4 O7 glasses were prepared by melt-quenching and characterized by X-ray diffraction, density measurements, infrared spectroscopy, diffuse reflectance ultraviolet–visible spectroscopy, and magnetic measurements. Results show that addition and successive increase of cobalt oxide determines important properties of the glasses. An increase in cobalt oxide concentration converted BO4 structural units into BO3 units and led to intensification of magnetic interactions between cobalt ions. The presence of cobalt(III) in glasses was confirmed by optical spectroscopy and magnetic data.